Atom‐Resolved Investigation on Dynamic Nucleation and Growth of Platinum Nanocrystals (Small Methods 6/2022). Issue 6 (15th June 2022) - Ye, Huanyu; Yang, Feng; Sun, Yinghui; Wang, Rongming
Abstract : Inside Front Cover In article number 2200171, Sun, Wang, and coworkers focused on the nucleation and growth mechanism of nanocrystals. The dynamic transformation of a solid‐phase model platinum precursor was investigated at atomic resolution. Those findings shall provide a deeper understanding of the solid‐phase nucleation mechanism. The in‐situ method can be applied to study the nucleation process of other systems.